Beneficial effects of eculizumab regardless of prior transfusions or bone marrow disease: Results of the International Paroxysmal Nocturnal Hemoglobinuria Registry. (11th August 2020) - Röth, Alexander; Araten, David J.; Larratt, Loree; Kulasekararaj, Austin G.; Maciejewski, Jaroslaw P.; Wilson, Amanda; Gustovic, Philippe; Kanakura, Yuzuru
Abstract: Objectives: To evaluate the effects of eculizumab on transfusions and thrombotic events (TEs) in patients with and without prior history of transfusion in the International Paroxysmal Nocturnal Hemoglobinuria (PNH) Registry. Methods: Registry patients enrolled on or before January 1, 2018, initiated on eculizumab no more than 12 months prior to enrollment, having known transfusion status for the 12 months before eculizumab initiation, and ≥12 months of Registry follow‐up after eculizumab initiation, were included. Results: Eculizumab treatment was associated with a 50% reduction in transfusions in patients with a transfusion history (10.6 units/patient‐year before eculizumab vs 5.4 after; P  < .0001), with greater reduction observed in those with no history of bone marrow disease vs those with bone marrow disease. Mean lactate dehydrogenase levels decreased from a mean of 6.7 to 1.4 times the upper limit of normal (ULN) in patients with transfusion history and from 5.1 to 1.2 times ULN in those with no transfusion history. TE and major adverse vascular event rates also decreased by 70% in patients with and without history of transfusion. Conclusions: The benefit of eculizumab therapy does not appear to be limited to any group defined by transfusion history or bone marrow disease history.